Analisis Pelaksanaan Akad Murabahah di Koperasi Jasa Keuangan Syariah BMT Mandiri Sejahtera Jawa Timur - Al Maghfuri, Rahmah Salsabila; Wulandari, Laura Ayu; Rahmawati, Rahmawati; Putri, Stalis Manzila; Qur'ani, Nuzulia (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
Murabahah financing is basically a form of buying and selling with a profit margin system. This study was conducted to determine the implementation of the murabahah contract at KJKS BMT Mandiri Sejahtera East Java. Qualitative research methods were carried out by surveys, interviews and documentation. The results of the murabahah financing study carried out by KJKS BMT Mandiri Sejahtera East Java are buying and selling financing with goods traded in the form of gold.